Efektivitas metode psyeducation games dalam meningkatkan motivasi belajar dan minat membaca Al-Quran di TPQ Baiturrohman - Tasykira Putri Aulia; Siska Rahma M.; Devia Mustafida; Rizal Basry Dunggio; Ichsanudin Robbani (Altruis: Journal of Community Services, 2022)
Individual success in learning is not only influenced by their potential but also their motivation to learn and interest in reading. On the one hand, based on an assessment conducted on children in TPQ Baiturrohman, Precet Village, it was found that their learning motivation and interest in reading were still low. Psyeducation games were carried out in order to increase learning motivation and interest in reading for TPQ Baiturrohman children. The activity involved 32 TPQ Baiturrohman children aged 4-14 years. The results of t-test showed that the Psyeducation games activities proved effective in increasing the learning motivation and interest in reading of the children of TPQ Baiturrohman.